L'aspettualità nel contatto linguistico: lingue slave e oltre Resistenza, ristrutturazione ed innovazione dell'aspetto verbale e della sua periferia sotto l'influsso di varietà alloglotte. Atti del 3º Convegno Internazionale Costanza/Hegne, 16-20 giugno 2019 - Breu, Walter; Pila, Malinka (Biblioteca di Studi Slavistici, 2023)
This volume investigates the functional-semantic field of aspectuality in relation to the role of language contact in the development of minority languages in Italy and beyond, highlighting hitherto completely unknown parallels, e.g. contact-induced development of progressive and prospective verbal periphrases. The influences of the dominant languages surface not only in Slavic derivational verbal aspect, but also in the restructuring of morphosyntactic reflexes of aspect. Aspectuality is examined in relation to Slavic micro-languages spoken in Italy (Molise Slavic, Resian, Tersko, Nadiško), Austria (Burgenland Croatian), Germany (Upper Sorbian), Albania (Kaj-nas) and the Baltic, as well as in relation to Arbëresh, Cimbrian, Griko, Lithuanian and Macedonian.